Neurological manifestations and complications of COVID-19. A literature review - Aleksandra Maria Krasa; Magdalena Kozioł; Halina Piecewicz-Szczęsna; Anna Łopuszyńska; Ewa Piekarska; Piotr Więsyk; Mateusz Pawlicki (Kazimierz Wielki University, 2021)
Introduction. The first case of SARS-CoV-2 infection was identified in December 2019 in Wuhan, China. The disease spread rapidly worldwide and the WHO declared a pandemic on March 11, 2020. Although coronavirus disease 2019 (COVID-19) has been associated primarily with respiratory disorders, more and more research is focusing on neurological manifestations and complications. Objective. The aim of the review is to systematize and update the knowledge and available research on neurological complications among COVID-19 patients. Review methods. A systematic search of PubMed and Google Scholar databases was conducted for studies. The following keywords combinations were used: COVID-19, SARS-CoV-2 infection, neurological complications, neurological manifestations, neuroinvasion, neurovirulence. Results. The disease in most patients is characterized by mild to medium fever, fatigue, dry cough, dyspnea, muscle pain and headache. ACE2, which is the receptor for SARS-COV-2, is ubiquitously expressed in a variety of human organs, including the brain. Following previous reports, these receptors are expressed in both glial cells and neurons. Many studies have reported neurological symptoms and complications among  COVID-19 patients. The reported manifestations include: smell and taste disturbance, non-specific symptoms such as myalgia, headache and dizziness, acute cerebrovascular complications, encephalopathy, meningoencephalitis/encephalitis, seizure and complications of the peripheral nervous system. Conclusion. Healthcare professionals dealing with COVID-19, neuroscientists, and the general public should be aware of the neurological complications of COVID-19. Further studies are needed to assess the incidence of COVID-19 neurological complications in different populations and  more analyzes are also required to understand the detailed mechanism of how the virus affects the nervous system.